"Big" Continuous Restrictions of Arbitrary Functions. Issue 6 (3rd July 2019) - Ciesielski, K. C.; Martínez-Gómez, M. E.; Seoane-Sepúlveda, J. B.
Abstract: We discuss an amazing 1922 result of Henry Blumberg that for an arbitrary f : R → R, there is a dense D ⊂ R such that the restriction f ↾ D is continuous . In particular, we provide a new short proof of this theorem.